Activation of the Aryl Hydrocarbon Receptor Ameliorates Acute Rejection of Rat Liver Transplantation by Regulating Treg Proliferation and PD-1 Expression. Issue 11 (16th June 2022) - Cao, Wanyue; Lu, Jing; Li, Lei; Qiu, Chen; Qin, Xuebin; Wang, Tao; Li, Shanbao; Zhang, Jinyan; Xu, Junming
Abstract : Background: Aryl hydrocarbon receptor (AhR) plays important roles in modulating immune responses. However, the role of AhR in rat liver transplantation (LT) has not been explored. Methods: Safety and side effects of N -(3, 4-dimethoxycinnamonyl) anthranilic acid (3, 4-DAA) and 2-methyl-2H-pyrazole-3-carboxylic acid amide (CH223191) were evaluated. We used optimal doses of 2 drugs, 3, 4-DAA, a drug used for mediating AhR activation, and CH223191, antagonist of AhR (3, 4-DAA, CH223191, and 3, 4-DAA + CH223191), intraperitoneally administered to recipients daily to investigate the role of AhR in the rat LT model. The recipient livers were used to observe the pathological changes, the cells infiltrating the graft, and changes of AhR and programmed death-1 (PD-1) by Western blot, real-time polymerase chain reaction, and immunofluorescence assays. The contents of Foxp3 + and PD-1 + T cells in the recipient spleen and peripheral blood mononuclear cells were evaluated by flow cytometry. In vitro, after isolating CD4 + T cells, they were treated with different AhR ligands to observe the differentiation direction and PD-1 expression level. Results: The activation of AhR by 3, 4-DAA prolonged survival time and ameliorated graft rejection, which were associated with increased expression of AhR and PD-1 in the livers and increased Foxp3 + T cells and PD-1 + T cells in recipient spleens, livers, and peripheral blood mononuclear cells. In vitro, primary T cells incubated with 3, 4-DAA mediated increased proportion of Treg and PD-1 + T cells. However, the suppression of AhR with CH223191 reverses these effects, both in the LT model and in vitro. Conclusions: Our results indicated that AhR activation might reduce the occurrence of rat acute rejection by increasing the proportion of Treg and the expression of PD-1.